The Effects of Wetted Ice on Dynamic Stability over a Rewarming Period - Jill Alexander; Youl Mawene; Jenny Alexanders; Josh Jeffery; David Rhodes (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
BACKGROUND During half time or breaks in play cryotherapy is often applied for analgesia for minor musculoskeletal sport injury, however the effect of cryotherapy on dynamic stability is debated. A risk factor for further lower limb injury may be heightened due to a reduction in dynamic postural stability. OBJECTIVES The purpose of the current study was to investigate the effects of wetted-ice applied for 20-minutes at the ankle on dynamic stability using the star excursion balance test, immediately-post exposure and over a rewarming period of 30-minutes. MATERIALS AND METHODS Twenty-two healthy male athletes that regular took part in land-based sport were assessed on reach directions of Anterior (Ant), Posteromedial (PM), and Posterolateral (PL) using the modified star excursion balance test (mSEBT) on the non-dominant limb. Thermal imaging quantified skin surface temperature (Tsk) over lateral and medial regions. Participants were tested pre-intervention, exposed to 15-minutes wetted-ice cryotherapy application, immediately-post and up to 30-minutes post intervention at 10-minute intervals. RESULTS Significant decreases in Tsk over the medial and lateral regions of the ankle (p < 0.05) not returning to pre-cooling temperatures at 30-minutes post. Significant decrease in reach -distance scores (ANT, PL and PM) pre-immediately post and at 10, 20 and 30-minutes post cryotherapy exposure. CONCLUSION Following wetted ice application to the non-dominant ankle, dynamic postural stability was adversely affected for up to 30-minutes post exposure demonstrated through a decrease in reach scores for ANT, PL and PM directions. Functional performance which requires stabilising mechanisms may be negatively affected and contribute to a heightened risk of injury or further injury in consideration of the findings.